ROLE OF EPIDERMAL GROWTH FACTOR RECEPTOR AND KI67 IN EPITHELIAL OVARIAN TUMOR - Pathak, Ankita; Singh, Mahendra; Verma, Neelima (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study was to evaluate epidermal growth factor receptor (EGFR) and Ki67 expression in epithelial ovarian tumors and assess the existence of any correlation between overexpression of these markers and histological grades. Methods: This prospective study was conducted in the Department of Pathology in a tertiary care hospital of G.S.V.M. Medical College from 2022 to 2024. The study included 50 patients with histologically confirmed epithelial ovarian tumors, whose post-resection specimens were subjected to immunostaining to determine the degree of expression of EGFR and Ki67 proliferation index. Details were noted pertaining to age, tumor type, and histological grade. Statistical analysis included the Chi-square test, which evaluated associations between age, histological grade, EGFR expression, and Ki67 proliferation index. Results: Most of the participants were below 60 years of age (80%). Most tumors were benign (72%), with serous cystadenoma being the most common (66%). The association between histological grade and age was statistically significant; with benign tumors being more common in patients aged ≤50 years and malignant tumors more frequent in those aged >50 years (p=0.018). EGFR expression was observed in 18% of the tumors, predominantly malignant ones, showing a significant association with tumor malignancy (p<0.001). In addition, the Ki67 proliferation index was significantly higher in malignant tumors (p<0.001), and its levels were associated with EGFR expression (p=0.026). Conclusion: The study findings suggest that molecular markers such as EGFR and Ki67 may be useful in predicting tumor behavior and guiding tailored treatment strategies for ovarian cancer patients.